(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
Crime Fiction is a genre that some people do not value at all. On the other hand, many people find it entertaining and such sophisticated authors as Borges or Umberto Eco write Crime Fiction and do not consider it ‘evil’ to master this form of art. This genre might hide genuine treasures for the reader to find. Lawrence Block Bernie Rhodenbarr’s fiction series (whose protagonist is a bibliophile burglar), recreates the intellectual excitement that used to be part of crime fiction reading in the past. Through his writings the author initiates us in the realms of libraries and reading in an entertaining way. We encounter the libraries visited by the burglars as well as the books they can find there. We also learn about the personalities and the reading habits of the second hand bookshops’ visitors. The ‘unhidden’ objective of this writing is to popularise both Crime Fiction as a genre and Rhodenbarr’s Crime Fiction series to the reader and to the professional librarian.